Resilient actions in the diagnostic process and system performance. Issue 12 (27th June 2013) - Smith, Michael W; Davis Giardina, Traber; Murphy, Daniel R; Laxmisan, Archana; Singh, Hardeep
Abstract : Objectives: Systemic issues can adversely affect the diagnostic process. Many system-related barriers can be masked by 'resilient' actions of frontline providers (ie, actions supporting the safe delivery of care in the presence of pressures that the system cannot readily adapt to). We explored system barriers and resilient actions of primary care providers (PCPs) in the diagnostic evaluation of cancer. Methods: We conducted a secondary data analysis of interviews of PCPs involved in diagnostic evaluation of 29 lung and colorectal cancer cases. Cases covered a range of diagnostic timeliness and were analysed to identify barriers for rapid diagnostic evaluation, and PCPs' actions involving elements of resilience addressing those barriers. We rated these actions according to whether they were usual or extraordinary for typical PCP work. Results: Resilient actions and associated barriers were found in 59% of the cases, in all ranges of timeliness, with 40% involving actions rated as beyond typical. Most of the barriers were related to access to specialty services and coordination with patients. Many of the resilient actions involved using additional communication channels to solicit cooperation from other participants in the diagnostic process. Discussion: Diagnostic evaluation of cancer involves several resilient actions by PCPs targeted at system deficiencies. PCPs' actions can sometimes mitigate system barriers to diagnosis, and thereby impact the sensitivity of 'downstream' measures (eg, delays) in detecting barriers. While resilient actions might enable providers to mitigate system deficiencies in the short run, they can be resource intensive and potentially unsustainable. They complement, rather than substitute for, structural remedies to improve system performance. Measures to detect and fix system performance issues targeted by these resilient actions could facilitate diagnostic safety.